Therapeutic Strategies in Managing Acute Paraquat Poisoning: A Review Study: Therapeutic strategies in Paraquat poisoning - Majidi, Mohammad (International Journal of Medical Toxicology and Forensic Medicine, 2021)
Background: Paraquat is an extremely toxic herbicide that causes such severe adverse effects as acute lung injury, pulmonary fibrosis, metabolic acidosis, cardiogenic shock, acute renal failure, and even death. Regarding the high prevalence and mortality rate without a specific antidote in paraquat poisoning, we explored managing acute paraquat poisoning. Methods: In this study, required articles were searched using the following keywords: “paraquat poisoning” and “treatment” on an electronic database, such as Pubmed and Google Scholar from January 2013 to December 2020. Results: This article examined pharmacokinetic, clinical, and laboratory findings, complications, diagnosis, prognostic factors, and the treatment of paraquat poisoning. Then, the medical management and therapeutic procedures of paraquat poisoning were discussed. Conclusion: Although there exists no antidote for paraquat poisoning, numerous therapeutic methods have been suggested for treating paraquat poisoning. However, their efficacy remains undiscovered. An interesting finding in one study indicating that endotracheal intubation is an inappropriate procedure for managing paraquat poisoning; further studies are required in this regard. For these reasons, preventing poisoning and using other herbicides with less toxicity than paraquat are recommended.